Comparison of antiplatelet effects of prasugrel and ticagrelor in cynomolgus monkeys by an ELISA-based VASP phosphorylation assay and platelet aggregation - Tomizawa, Atsuyuki; Ohno, Kousaku; Jakubowski, Joseph A.; Mizuno, Makoto; Sugidachi, Atsuhiro (Thrombosis and Haemostasis, 2013)
Prasugrel is the third generation thienopyridine prodrug, and ticagrelor is a non-competitive direct acting P2Y12 antagonist. In phase 3 studies, both agents reduced ischaemic event rates compared to clopidogrel. The present in vitro human and monkey studies showed that ticagrelor’s active metabolite (AM) was more potent than ticagrelor and prasugrel’s AM on inhibition of ADP-induced platelet aggregation by light transmission aggregometry and ELISA-based vasodilatorstimulated phosphoprotein (VASP) phosphorylation assay. In contrast, on an oral dosage basis (mg/kg), prasugrel showed more potent platelet inhibition compared to ticagrelor on ex vivo aggregation and VASP phosphorylation assays in monkeys. Single oral doses of prasugrel (0.3 and 1 mg/kg) resulted in robust antiplatelet effects, which were sustained up to 24 hours after administration. Ticagrelor (3 and 10 mg/kg, p.o.) also showed significant antiplatelet effects but its effects were diminished at 24 hours after the dosing. Repeat administration of prasugrel (1.8 mg/kg loading dose [LD], 0.3 mg/kg once daily maintenance dose [MD]) showed more rapid antiplatelet effects and longer duration of action throughout the entire day. Twice a day repeat administration of ticagrelor (10 mg/kg bid MD following a single 20 mg/kg LD) also showed significant antiplatelet effects but with more intra-day variability compared to prasugrel. The in vitro and ex vivo studies showed strong correlations between platelet aggregation and VASP phosphorylation for prasugrel, ticagrelor and their AMs. These strong correlations between platelet aggregation and VASP phosphorylation in non-human primates also suggest that ELISA-based human VASP assay can be utilised for non-human primate platelet studies.
Keywords: P2Y12 antagonist; VASP; prasugrel; ticagrelor; platelet aggregation